PROS AND CONS OF CASH WAQF LINK SUKUK IN INDONESIA: ANALYSIS OF REGULATIONS, POTENTIAL, AND CHALLENGES - Khoirunnisa, Nur Awali (JURNAL ILMIAH EDUNOMIKA, 2025)
Cash waqf is a contemporary innovation in Islamic philanthropy, where the object of waqf is no longer limited to physical assets but also includes financial instruments such as cash and sharia securities. This study aims to analyze the pros and cons of implementing Cash Waqf Link Sukuk in Indonesia, particularly in the context of regulations, economic development potential, and operational and sharia challenges. The research method employs a descriptive qualitative approach with content analysis techniques applied to primary literature (fatwas from the DSN-MUI, Law No.41/2004, BWI Regulations) and secondary literature (journals, sharia financial reports). The research findings indicate that Cash Wakaf Link Sukuk has a strong legal foundation through the Wakaf Law and BWI Regulations, with a mechanism for managing wakaf funds invested in government sukuk. This scheme offers the following benefits: (1) stable returns from sukuk coupons, (2) flexibility in allocating funds for social-productive projects, and (3) transparency through oversight by authoritative institutions. However, the main challenges include: (1) low public literacy regarding investment-based wakaf products, (2) liquidity risks and sukuk value fluctuations, and (3) sharia-related controversies regarding the ownership status of wakaf assets within the sukuk structure. The implications of this research provide policy recommendations in the form of strengthening socialization, synergy between BWI and the Financial Services Authority (OJK), and improving the benefit distribution model to be in line with sharia objectives. These findings contribute to the development of sharia financial literacy and modern waqf governance in Indonesia.